The Cause for Heart Disease and Strokes - Kummerow, Fred A. (Journal of Nutritional Therapeutics, 2013)
There has been no solution to heart disease to date. I obtained discarded veins from bypass (CABG) surgeries and subjected them to phospholipid analysis. We also obtained arterial cells from human umbilical cords and cultured them with a decreasing concentration of either cholesterol or oxidized cholesterol. Patients undergoing CABG surgery and aging swine had significantly higher levels of sphingomyelin in their arterial cells than arterial cells from human umbilical cords. Oxidized low-density lipoprotein (OxLDL) and oxysterols further contribute to atherosclerosis by increasing the synthesis of thromboxane in platelets, a clotting factor. When we incubated arterial cells with cholesterol that had not been oxidized, even at twelve times the concentration of the oxidized cholesterols we used, there was no effect on sphingomyelin content, this shows that cholesterol itself is not the reason for heart disease, and has to be oxidized in order to cause harm. My study indicated that atherosclerosis is due to a diet that contains a high level of oxysterols. Normal levels of oxysterols in the plasma will not increase sphingomyelin levels. Removing oxidized fat from the diet should be considered as a therapeutic measure for atherosclerosis. Ancel Keys, who some consider the father of the cholesterol-heart disease hypothesis said in 1997: "There's no connection whatsoever between the cholesterol in food and cholesterol in the blood."